2010
DOI: 10.1155/2010/496829
|View full text |Cite
|
Sign up to set email alerts
|

Suspected Nonalcoholic Fatty Liver Disease Is Not Associated with Vitamin D Status in Adolescents after Adjustment for Obesity

Abstract: This study investigated a potential independent association between hypovitaminosis D and suspected nonalcoholic fatty liver disease (NAFLD) in a nationally representative sample of the US adolescents. Data from 1630 subjects 12–19 years of age were examined using the National Health and Nutrition Examination Survey, 2001–2004. The vitamin D status of subjects was categorized into quartiles of serum 25-hydroxyvitamin D. Subjects with serum ALT > 30 U/L were classified as having suspected NAFLD. Data regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…An association between NAFLD and low 25(OH)D levels, independent from that between NAFLD and altered glucose homeostasis parameters, has been observed in a general population [5]. This finding was not confirmed in adolescents, in whom vitamin D status was not independently associated with NAFLD after adjusting for obesity [17]. Targher et al reported that among NAFLD patients with chronically elevated liver enzymes who underwent liver biopsy, significantly lower 25(OH)D concentrations were closely associated with histologic severity of hepatic steatosis, independent of age, insulin resistance or body mass index [18].…”
Section: Discussionmentioning
confidence: 88%
“…An association between NAFLD and low 25(OH)D levels, independent from that between NAFLD and altered glucose homeostasis parameters, has been observed in a general population [5]. This finding was not confirmed in adolescents, in whom vitamin D status was not independently associated with NAFLD after adjusting for obesity [17]. Targher et al reported that among NAFLD patients with chronically elevated liver enzymes who underwent liver biopsy, significantly lower 25(OH)D concentrations were closely associated with histologic severity of hepatic steatosis, independent of age, insulin resistance or body mass index [18].…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, in two studies using B-mode ultrasound NAFLD diagnosis (again from Italy and the USA), serum vitamin D was also found to be an independent predictor of NAFLD [19,20] . However, the inverse relationship that was shown to exist between serum levels of vitamin D and an unexplained elevation in ALT [9] was found to disappear in an adolescent population study after adjustment for obesity [21] . Moreover, when an Italian study of essential hypertension performed an analysis of NAFLD, the association with vitamin D deficiency was Data are presented as mean±SD or median (interquartile range).…”
Section: Discussionmentioning
confidence: 90%
“…Another study performed with a small number (162) of participants with NAFLD also reported an association of low 25(OH) D levels with the presence of NAFLD, independent of metabolic syndrome, diabetes or insulin resistance [22]. In contrast, a very recent study conducted using the National Health and Nutrition Examination Survey database of 1,630 American adolescents found that, after adjustment for obesity, vitamin D levels were not associated with suspected NAFLD assessed only by elevated ALT levels [20]. The authors commented that their study population was larger than those in previous studies, and that adult results might not be applicable in the adolescent population, as adults may have other confounding factors that cannot be considered in these kinds of analyses.…”
Section: Discussionmentioning
confidence: 95%
“…Because inflammation and oxidative stress might act as the common pathogenic mechanisms of NAFLD and vitamin D deficiency, and as both diseases are associated with insulin resistance, type 2 diabetes and cardiovascular disease, studies have been recently performed to examine the relationship of vitamin D levels with the development of NAFLD [17][18][19][20][21][22]. Previous studies showed that low vitamin D levels were associated with the development of NAFLD, although the numbers of subjects included in the studies were small [17,18,22].…”
Section: Anthropometric and Laboratory Measurementsmentioning
confidence: 99%